Family formation preferences of older adolescent students at the University of the Philippines-Diliman - Gonzales, Jeremia Oanes
The present study explored the concept of family formation among older adolescents. It aimed to identify their preferred age and type of family structure in starting their own family;determine the influence of their family of origin to their concept of family formation; and compare the concept of family formation between males and females and between adolescents from intact and non-intact families. On hundred twenty male and female students of the University of the Philippines - Diliman from intact and non-intact families, aged 18-20 years old, were purposively selected to answer the questionnaires. Twenty students (five males and females from intact and 5 males and females from non-intact families) among the survey respondents were interviewed . The data obtained were analyzed using frequency tables and thematic analysis. Results showed that older adolescents delay their timing of family formation due to factors such as their family, peers, social organizations, individual readiness, and personal inclinations (mean preferred age: male intact = 28, male non-intact = 29, female intact = 28, female non-intact = 26). Intact family is still the most preferred type regardless of the family structure where the older adolescents came from. Findings also showed the similarities and differences in the concept of family formation between males and females. There are no observed differences in the concept of family formation among the respondents from intact and non-intact families. The family of origin is revealed to be influential to the family formation preferences of the older adolescents. Thus, educating families about the different aspects of family life should be considered.